Transplantation related toxicity and mortality in older autologous hematopoietic cell transplantation recipients. Issue 9 (19th July 2017) - Belete, Hewan; Burns, Linda J.; Shanley, Ryan; Nayar, Manju; McClune, Brian; Lazaryan, Aleksandr; Bachanova, Veronika; Bejanyan, Nelli; Ustun, Celalettin; Brunstein, Claudio; Weisdorf, Daniel J.; Arora, Mukta
Abstract: With advances in supportive care, autologous hematopoietic cell transplant (AHCT) is increasingly being performed for patients older than 60 years. We analyzed patients receiving an AHCT for multiple myeloma or lymphoma in a contemporary cohort (2010–2012), with consistent treatment and supportive care and compared outcomes [CTCAE grade 3–5 toxicities, nonrelapse mortality (NRM) and overall‐survival (OS)] of younger (40–59 years, n  = 77) versus older (≥60 years, n  = 67) recipients. The proportion of patients with neutropenic infections was higher in the older group (64% vs. 44%; P  = 0.02). The proportion of patients with any grade 3–5 toxicity was also higher in the older group (84% vs. 67%, P  = 0.03). In multivariate analysis, older age was significantly associated with higher odds (OR: 2.57, 95% CI:1.09–6.05) of grade 3–5 toxicity. The NRM was 3% (older) vs. 0% (younger) at 1 year. The probability of OS at 2 years was lower in the older group (76% vs. 90%, P  = 0.04). Though AHCT can be performed safely in older recipients, the higher toxicity and slightly higher NRM in this population needs attention. Studies focusing on risk‐stratification in older patients would further help predict toxicity. Further studies addressing enhanced supportive care needs for older patients who are most likely to benefit are indicated.